PEMEC electrode for constructing three-dimensional catalyst layer on ordered diffusion layer and preparation method of PEMEC electrode

By structuring a three-dimensional microstructure on the diffusion layer of the PEMEC electrode, the problem of insufficient contact area between the catalyst layer and the diffusion layer is solved, the electrolytic performance and catalyst utilization rate are improved, the Ir usage is reduced, and the efficient electrolytic performance is achieved.

CN119265598AActive Publication Date: 2025-01-07TSINGHUA UNIVERSITY
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411254800.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-09
Publication Date
2025-01-07
Estimated Expiration
2044-09-09

AI Technical Summary

Technical Problem

In the existing PEMEC electrode, the contact area and binding strength of the catalyst layer and the diffusion layer are insufficient, resulting in low electrolytic performance and high cost of high IrO2 content. In addition, the traditional porous transmission electrode forms a catalyst island at irregular PTL trenches, affecting electrolysis. Water performance.

Method used

A three-dimensional microstructure is constructed on the diffusion layer of the PEMEC electrode, including mechanical embossing, laser engraving and irregular chemical corrosion shapes, forming a three-dimensional catalyst layer to improve the contact area and bonding strength between the catalyst layer and the diffusion layer.

Benefits of technology

The electrolytic performance of the electrode is improved, the Ir usage is reduced, the catalyst utilization rate is enhanced, and the process is simple, and high temperature conditions or electrochemical reactions are not required, showing electrolytic activity exceeding the standard porous transport electrode.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119265598A_ABST
    Figure CN119265598A_ABST
Patent Text Reader

Abstract

The invention provides a PEMEC electrode for constructing a three-dimensional catalyst layer on an ordered diffusion layer and a preparation method. A diffusion layer of the PEMEC electrode has a three-dimensional microstructure, and a supported catalyst layer is a three-dimensional catalyst layer; the three-dimensional microstructure comprises one or a combination of more than two of mechanical embossing, laser engraving and irregular chemical corrosion shapes. According to the technical scheme provided by the invention, the three-dimensional microstructure is constructed on the PTL substrate in advance by adopting physical, chemical and other modes, then the catalyst layer is coated on the basis of the PTL substrate, and the PTE with the three-dimensional catalyst layer is prepared, so that the material process design aiming at the catalyst microstructure is omitted, the contact area between the catalyst layer and the PTL is increased, and the production efficiency is improved. And the water electrolysis performance is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a PEMEC electrode for constructing a three-dimensional catalyst layer on an ordered diffusion layer and a preparation method thereof, belonging to the technical field of water electrolysis. Background Art

[0002] As the upstream of the hydrogen energy industry chain, hydrogen production determines the properties of hydrogen energy and the cost of hydrogen use. Among them, the proton exchange membrane (PEM) electrolyzer (PEMEC) is one of the most promising green hydrogen production technologies due to its advantages such as high current density, high hydrogen purity and fast dynamic response. The core component of the electrolyzer is the electrode, which consists of PEM, catalyst layer and diffusion layer (PTL). The PEM plays the role of transferring protons. The catalyst layers on both sides of the PEM are the places where the water electrolysis reaction occurs. The PTL outside the catalyst layer conducts electrons and transmits water / gas.

[0003] Since PEMEC uses perfluorinated membrane materials, the electrolyte is highly acidic. For catalytic activity and durability considerations, the anode is usually made of high-content IrO2 (2-4 mg cm -2 ). The cost of Ir is very high, so it is crucial to improve the efficiency of hydrogen production by water electrolysis while ensuring low Ir usage.

[0004] At present, the most common method of preparing membrane electrodes is to coat the catalyst on the PEM to obtain a CCM membrane electrode, whose catalyst layer is a planar structure, while the PTL is a three-dimensional structure. A high catalyst loading is required to increase the thickness of the catalyst layer in order to achieve contact between the catalyst layer and the PTL, and the low catalyst utilization rate causes waste. In addition, the catalyst can also be coated on the PTL to obtain a porous transport electrode (PTE). At this time, the catalyst layer adheres to the surface of the PTL to form a three-dimensional structure. Although the amount of Ir can be greatly reduced, catalyst islands will be formed in the irregular grooves of the PTL, resulting in the attenuation of the electrolytic water performance.

[0005] In order to solve the above problems, a design method to increase the contact area of ​​the catalyst layer in the electrode is urgently needed. Summary of the invention

[0006] In order to solve the above technical problems, the purpose of the present invention is to provide a PEMEC electrode and a preparation method thereof, which can increase the contact area and bonding strength between the catalyst layer and the diffusion layer by constructing a microstructure on the diffusion layer of the electrode, thereby improving the water electrolysis performance of the electrode.

[0007] To achieve the above object, the present invention first provides a PEMEC electrode having a three-dimensional catalyst layer constructed on an ordered diffusion layer, wherein the diffusion layer of the PEMEC electrode has a three-dimensional microstructure, and the catalyst layer loaded is a three-dimensional catalyst layer;

[0008] The three-dimensional microstructure includes one or a combination of two or more of mechanical embossing, laser engraving and irregular chemical etching shapes.

[0009] In the above-mentioned PEMEC electrode, preferably, the three-dimensional microstructure includes: mold mechanical embossing (blade-shaped, with a width of 10-30 μm, a blade spacing of 20-100 μm, and the embossing arrangement is parallel and / or staggered, and the staggered shape means that the embossings are cross-distributed at a certain angle, such as 30-90°), various shapes of laser engraving shapes (quadrilaterals, circles, etc., also referred to as lines) and irregular chemical corrosion shapes. One or a combination of more than two. Among them, the mechanical embossing with a width of 10 μm and staggered arrangement shows the best electrolytic water activity.

[0010] In the above-mentioned PEMEC electrode, preferably, the diffusion layer is a titanium mesh with a mesh size of 40-600 meshes (more preferably 200 meshes) and a thickness of 0.1-1.0 mm (more preferably 0.4 mm).

[0011] In the above PEMEC electrode, preferably, the material of the catalyst layer is IrO2, and the loading amount is 0.5-4 mg·cm -2 , more preferably 2 mg·cm -2 .

[0012] The present invention also provides a method for preparing the PEMEC electrode having a three-dimensional catalyst layer constructed on the ordered diffusion layer, which comprises the following steps:

[0013] A three-dimensional microstructure is formed on the diffusion layer, and then a catalyst layer is coated to form a three-dimensional catalyst layer to obtain the PEMEC electrode.

[0014] In the above preparation method, preferably, the three-dimensional microstructure is formed by physical and / or chemical means.

[0015] In the above preparation method, preferably, the physical method includes embossing and / or laser etching.

[0016] In the above preparation method, preferably, when the embossing method is adopted, the mold used is a blade-shaped mold, which includes two opposite flat plates, each of which has a plurality of blade-shaped structures (e.g. Figure 3 As shown), the blade-shaped bottom side length is 1mm, the height is 1mm, the blade spacing is 1mm, and the blade-shaped structures are distributed in parallel; the pressure used during embossing is 2-10MPa. By controlling the specific process parameters of embossing, the shape and size of the PTL embossing can be adjusted to obtain a PTL substrate with different embossings, and further coated with a catalyst layer to obtain a PTE with a three-dimensional catalyst layer.

[0017] In the above preparation method, preferably, the chemical method includes chemical corrosion, such as etching with one or a combination of hydrofluoric acid, ammonium fluoride, ammonium bifluoride, hydrofluoric acid, lithium fluoride, sodium fluoride, potassium fluoride. Preferably, immersion is performed with hydrofluoric acid having a concentration of 0.1 mol / L, and the amount used is 40 mL of hydrofluoric acid for 100 mg of titanium mesh.

[0018] The above-mentioned PEMEC electrode provided by the present invention is composed of a proton exchange membrane, two catalyst layers, and two diffusion layers, wherein the two catalyst layers are respectively located on both sides of the proton exchange membrane, and the two diffusion layers are respectively located on the outsides of the two catalyst layers. During the preparation process, the method provided by the present invention is first used to obtain a diffusion layer with a three-dimensional catalyst layer, and then the diffusion layer is loaded onto the two layers of the proton exchange membrane respectively, thereby obtaining a PEMEC electrode.

[0019] The technical solution provided by the present invention adopts physical, chemical and other methods to pre-construct a three-dimensional microstructure on a PTL substrate, and then coats a catalyst layer based on the PTL substrate to prepare a PTE with a three-dimensional catalyst layer, thereby eliminating the material process design for the catalyst microstructure, increasing the contact area between the catalyst layer and the PTL, and thereby improving the water electrolysis performance.

[0020] The technical solution of the present invention can bring the following beneficial effects:

[0021] (1) The PTE prepared by the present invention only requires a step of pre-treatment of PTL on the basis of traditional PTE preparation, and does not require high temperature conditions or electrochemical reaction participation, so the process is simple and the flow is clear.

[0022] (2) The PTE prepared in the present invention has a three-dimensional microstructure, which helps to increase the active area of ​​water electrolysis and thus improve the alkaline OER activity.

[0023] (3) The PTE prepared in the present invention exhibits water electrolysis activity in PEMEC that exceeds that of standard porous transport electrodes. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a light microscopic photograph of the untreated clean PTL used in Comparative Example 4;

[0025] Figure 2 Optical microscope and SEM photos of the embossed PTL substrates by mechanical embossing, laser engraving and chemical etching of Example 1 and Comparative Examples 1-3;

[0026] Figure 3 Schematic diagram of the blade-shaped mold used in Example 1 and Comparative Example 1;

[0027] Figure 4This is a SEM photo of the three-dimensional catalyst layer PTE after the catalyst layer is sprayed in Example 1;

[0028] Figure 5 PEMEC polarization curves of Example 1 and Comparative Examples 1-4;

[0029] Figure 6 is the double-layer capacitance (C dl ) curve and the calculated electrochemical active area (ECSA) results. DETAILED DESCRIPTION

[0030] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be construed as limiting the applicable scope of the present invention.

[0031] Example 1

[0032] This embodiment provides a three-dimensional PTE prepared by physical imprinting, and the preparation method thereof comprises the following steps:

[0033] The cut PTL (titanium mesh, 2×2cm 2 , mesh number is 200 mesh, thickness is 0.4 mm) and ultrasonically cleaned in acetone, ethanol, 2M HCl solution and deionized water in sequence for 5-30 min to obtain clean PTL;

[0034] Design and process a stainless steel stamping plate with a blade shape (bottom side length 1mm, height 1mm, blade spacing 1mm, parallel distribution);

[0035] The clean PTL and the stainless steel stamping plate were placed in a press, and pressure (5 MPa) was applied. The stainless steel stamping plate was translated and transposed, and the same pressure was applied to obtain a PTL with staggered embossing with an embossing interval width of 20 μm;

[0036] Take out the embossed PTL and spray the IrO2 catalyst layer with a loading of 2 mg cm -2 (based on the area of ​​the catalyst layer), a PTE with a three-dimensional catalyst layer was obtained.

[0037] Example 2

[0038] This embodiment provides a three-dimensional PTE prepared by physical imprinting. The difference between its preparation method and the preparation method of Example 1 is that the pressure applied by the press is different, which is 2 MPa in this embodiment; the rest is the same as Example 1.

[0039] Example 3

[0040] This embodiment provides a three-dimensional PTE prepared by physical imprinting. The difference between its preparation method and the preparation method in Example 1 is that the pressure applied by the press is different, which is 10 MPa in this embodiment, and the translation size of the imprinting plate after each imprinting is different, which is 60 μm in this embodiment; the rest is the same as in Example 1.

[0041] Example 4

[0042] This embodiment provides a three-dimensional PTE prepared by physical imprinting. The difference between the preparation method and the preparation method of Example 1 is that the translation size of the imprinting plate after each imprinting is different, which is 100 μm in this embodiment; the rest is the same as Example 1.

[0043] Example 5

[0044] This embodiment provides a three-dimensional PTE prepared by physical imprinting, which changes the translation size of the imprinting plate in Example 1 to 100 μm in this comparative example, and no transposition is performed after each imprinting to obtain a PTE with a three-dimensional catalyst layer. The other steps, process parameters, etc. are the same as those in Example 1.

[0045] Example 6

[0046] This embodiment provides a three-dimensional PTE prepared by laser engraving, and the preparation method thereof comprises the following steps:

[0047] The clean PTL obtained in Example 1 was prepared with a laser engraving machine to form square grooves (length and width of 100 μm, interval of 100 μm), with a laser power of 30 W and an etching time of 10 min; and then an IrO2 catalyst layer was sprayed with a loading of 2 mg·cm -2 (based on the area of ​​the catalyst layer), a PTE with a three-dimensional catalyst layer was obtained.

[0048] Example 7

[0049] This embodiment provides a three-dimensional PTE prepared by chemical etching, and the preparation method thereof comprises the following steps:

[0050] The clean PTL obtained in Example 1 was soaked in 0.1 mol / L hydrofluoric acid for 1 hour (40 mL hydrofluoric acid for 100 mg titanium mesh), taken out and washed; and then sprayed with an IrO2 catalyst layer with a loading of 2 mg cm -2 (based on the area of ​​the catalyst layer), a PTE with a three-dimensional catalyst layer was obtained.

[0051] Comparative Example 1

[0052] This comparative example provides a standard PTE, and its preparation method comprises the following steps:

[0053] The IrO2 catalyst layer was sprayed directly onto the clean PTL with a loading of 2 mg cm -2 (based on the area of ​​the catalyst layer) to obtain a standard PTE. The pretreatment method of PTL is consistent with the pretreatment method of Example 1.

[0054] Example 8

[0055] This embodiment provides a three-dimensional PTE prepared by physical imprinting. The difference between the preparation method of this embodiment and the preparation method of embodiment 5 is that the translation size of the imprinting plate after each imprinting is different (20 μm), and the rest is the same as embodiment 5.

[0056] Example 9

[0057] This embodiment provides a three-dimensional PTE prepared by laser engraving. The difference between the preparation method and the preparation method of Example 6 is that the laser engraving shape is circular (diameter 50 μm, interval 80 μm), and the rest is the same as Example 6.

[0058] The properties of the PTE prepared in Examples 1-9 and Comparative Example 1 were tested, and the specific structures are shown in Table 1.

[0059] Table 1

[0060]

[0061]

[0062] In Table 1, the microstructure size refers to the width of the cut, wherein, when the microstructure is blade-shaped, the microstructure size refers to the width of the blade cut; when the microstructure is square (square), the microstructure size refers to the side length of the square; when the microstructure is circular, the microstructure size refers to the diameter of the circle.

[0063] Figure 1 This is a light microscopic photograph of the untreated clean PTL used in Comparative Example 1.

[0064] Figure 2 The optical microscope and SEM images of the mechanically embossed, laser engraved and chemically etched embossed PTL substrates of Examples 1, 5-7 are shown.

[0065] Figure 3 Schematic diagram of the cross section of the stamping plate used in Examples 1-5 and 8. Figure 3 In the figure, the blades correspond to each other up and down, where d1 represents the length of the bottom side of the blade, d2 represents the distance between the blades, and h represents the height of the blade.

[0066] Figure 4 This is a SEM photograph of the three-dimensional catalyst layer PTE of Example 1 after the catalyst layer is sprayed.

[0067] Figure 5 ] are the PEMEC polarization curves of the PTEs of Examples 1, 5-7 and Comparative Example 1.

[0068] PEMEC polarization curve test method: The anode PTE electrodes prepared in this example and the comparative example were assembled in a PEM electrolyzer (active area of ​​4 cm 2 ) was tested in a single-sided CCM coated with a Pt / C catalyst (catalyst loading of 0.5 mg cm -2 ), the test temperature was 80°C, and the anode water circulation flow rate was 50 ml / min. The electrochemical workstation collected the voltammetric characteristic curve with a voltage range of 0-2.4 V and a scan rate of 5 mV / s.

[0069] Figure 6 is the double-layer capacitance (C dl ) curves and the calculated electrochemical active area (ECSA).

[0070] ECSA test method: The example and comparative example PTE were assembled in a PEM electrolyzer (4 cm 2 ) was tested in a single-sided CCM coated with a Pt / C catalyst on the cathode side, the test temperature was 80°C, and the anode water circulation flow rate was 50ml / min. The electrochemical workstation collected the voltammetric characteristic curve, the voltage range was 0-0.2V, the scan rates were 20, 40, 60, 80, 100, 120, and 140mV / s, and the current density of 0.1V was calculated to obtain the C of each sample at different scan rates. dl The standard electrochemical active area of ​​titanium mesh is 0.04 mF cm -2 According to the formula, the ECSA value of different titanium mesh PTE can be calculated (X ECSA ):

[0071]

[0072] ECSA=C dl (mF cm -2 ) / 0.04(mF·cm -2 )

[0073] Depend on Figure 2 It can be seen that the PTLs obtained in different embodiments and comparative examples have different morphologies at the micrometer scale.

[0074] Depend on Figure 4 It can be seen that after the catalyst is coated, the basic appearance of the microstructure can still be retained, with ups and downs in the three-dimensional spatial direction.

[0075] Depend on Figure 5It can be seen that the microstructures obtained by mechanical embossing, laser engraving and chemical etching are all helpful to improve the electrolytic water activity of PTE, among which the improvement effect of Example 1 is the most significant.

[0076] Depend on Figure 6 It can be seen that the microstructures obtained by mechanical embossing, laser engraving and chemical etching are all helpful to increase the ECSA of PTE, that is, the contact area between the catalyst and PTL, and thus increase the effective contact area between the electrode and the electrolyte; among them, the improvement effect of Example 1 is the most significant.

Claims

1. A PEMEC electrode having a three-dimensional catalyst layer constructed on an ordered diffusion layer, wherein: The diffusion layer of the PEMEC electrode has a three-dimensional microstructure, and the catalyst layer carried is a three-dimensional catalyst layer; The three-dimensional microstructure includes one or a combination of two or more of mechanical embossing, laser engraving and irregular chemical etching shapes.

2. The PEMEC electrode according to claim 1, wherein The mechanical embossing includes blade-shaped embossing, the width of the blade-shaped embossing is 10-30 μm, the blade spacing is 20-100 μm, and the embossing arrangement is parallel and / or staggered.

3. The PEMEC electrode according to claim 1, wherein The diffusion layer is a titanium mesh with a mesh size of 40 to 600, preferably 200, and a thickness of 0.1 mm to 1.0 mm, preferably 0.4 mm.

4. The PEMEC electrode according to claim 1, wherein The material of the catalyst layer is IrO2, and the loading amount is 0.5-4 mg·cm -2 , preferably 2 mg·cm -2 .

5. The method for preparing a PEMEC electrode having a three-dimensional catalyst layer constructed on an ordered diffusion layer according to any one of claims 1 to 4, comprising the following steps: A three-dimensional microstructure is formed on the diffusion layer, and then a catalyst layer is coated to form a three-dimensional catalyst layer to obtain the PEMEC electrode.

6. The preparation method according to claim 5, wherein: The three-dimensional microstructure is formed by physical and / or chemical means.

7. The preparation method according to claim 6, wherein: The physical method includes embossing and / or laser etching.

8. The preparation method according to claim 7, wherein: The mold used for the stamping is a blade-shaped mold, the bottom side length of the blade is 1 mm, the height is 1 mm, and the blade spacing is 1 mm; the blades are distributed in parallel.

9. The preparation method according to claim 7 or 8, wherein: The pressure used for the stamping is 2-10 MPa.

10. The preparation method according to claim 6, wherein: The chemical method includes chemical etching.

Citation Information

Patent Citations

  • Membrane electrode assembly with enhanced hydrophobicity and manufacturing method thereof

    CN103515623A

  • Ordered membrane electrode and preparation method thereof

    CN111740122A

  • Preparation method of three-dimensional structure membrane electrode of fuel cell

    CN115360396A

  • Membrane electrode assembly and preparation method thereof

    CN116190679A

  • Preparation method of anode catalyst layer of low-interface-impedance PEM water electrolysis membrane electrode

    CN116905002A